2019
DOI: 10.1007/s40094-019-00360-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of carbon monoxide gas adsorption on the Al2O3/Pd(NO3)2/zeolite composite film

Abstract: In this study, Al 2 O 3 /Pd(NO 3) 2 /zeolite composite films have been fabricated by roll coating method and characterized by X-ray diffraction, energy-dispersive X-ray spectroscopy and field emission scanning electron microscopy. The gas adsorption was tested in an experimental setup by a continuous gas analyzer KIMO KIGAZ 210 at constant temperature and pressure (32 °C and 1.5 bar) and as a function of reaction time (s). The inlet CO gas concentration was 150 mg L −1 , and the saturation level of CO gas conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…1-methyl-2-pyrrolidone (10cc) was added dropwise into the beaker containing γ-Al 2 O 3 and Zeolite, and kept on a magnetic stirrer (Model: HS 860). Stirring was continued for 1 h at room temperature in a closed beaker before the Al 2 O 3 /Zeolite was deposited on glass substrates by the roll-coating method [32]. To study CO adsorption capacity and efficiency of Al 2 O 3 /Zeolite composite films, four Al 2 O 3 /Zeolite coated substrates were used to make a hollow cubic container [32].…”
Section: Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…1-methyl-2-pyrrolidone (10cc) was added dropwise into the beaker containing γ-Al 2 O 3 and Zeolite, and kept on a magnetic stirrer (Model: HS 860). Stirring was continued for 1 h at room temperature in a closed beaker before the Al 2 O 3 /Zeolite was deposited on glass substrates by the roll-coating method [32]. To study CO adsorption capacity and efficiency of Al 2 O 3 /Zeolite composite films, four Al 2 O 3 /Zeolite coated substrates were used to make a hollow cubic container [32].…”
Section: Preparationmentioning
confidence: 99%
“…Zeolite adsorbent at a constant temperature and pressure. It is observed that over time the adsorbed CO concentration (mg L −1 ) increased while the speed of adsorption reduced due to the developing saturation level [32].…”
Section: Electron Dispersive X-ray Spectroscopy (Edx)mentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen, there is no obvious high intensity diffraction. All films have almost same pattern and exhibit only one broad diffraction peak at around 2θ=36°, which suggest that the Zr-Co-RE films are amorphous or nanocrystalline structure [17,32,38]. The full-width at half maximum (FWHM) of the peaks is 4.98 (0°), 5.73 (30°), 5.58 (60°), 4.38 (90°), respectively.…”
Section: Microstructure Characteristic Of Zr-co-re Getter Filmsmentioning
confidence: 99%